Evolution of a western Arctic ice-ocean boundary layer and mixed layer across a developing thermodynamically forced marginal ice zone - Gallaher, Shawn G. (Monterey, California. Naval Postgraduate School, 2016)
A comprehensive set of autonomous, ice-ocean measurements were collected across the Canada Basin to study the summer evolution of the ice-ocean boundary layer (IOBL) and ocean mixed layer (OML). Evaluation of local heat and freshwater balances and associated turbulent forcing reveals that melt ponds strongly influence the summer IOBL-OML evolution. The areal expansion and drainage of melt ponds resulted in a substantial increase in upper ocean heat storage (39 MJm-2) and development of the summer mixed layer and near-surface temperature maximum (NSTM). 1-D boundary layer model results show that melt pond drainage provided sufficient buoyancy to the summer halocline to prevent subsequent wind events from mixing out the NSTM. Ice Camp observations captured the development of a second shallower NSTM in late summer; however, meltwater contributions were inadequate to sustain this feature when winds increased. In the marginal ice zone (MIZ), thermal heterogeneities in the upper ocean led to large ocean-to-ice heat fluxes (100–200 Wm-2) and enhanced basal ice melt (3–6 cm-day-1). Calculation of the upper ocean heat budget shows that the extensive area of deteriorating sea ice observed away from the ice edge during the 2014 season, termed the thermodynamically forced MIZ, was driven primarily by local solar radiative heat input. . Approved for public release; distribution is unlimited. Commander, United States Navy http://archive.org/details/evolutionofweste1094550548